Productivity and profitability of pineapple smallholder's in Johor / Siti Nur Syuhada Mohamed Rahim - Mohamed Rahim, Siti Nur Syuhada (2017)
Johor is the main pineapple producer for Malaysia with the biggest cultivation area. However, Johor still faced a low productivity issue where the productivity level is 27.75 Mt/ha compared to the national target which is at 40 Mt/ha (Malaysian Pineapple Industry Board [MPIB], 2014). The low productivity issue is caused by the smallholders that work in less efficient manners and below the economic scale compared to the estate sectors. Thus, there is an urgent need to investigate the productivity and profitability level of the smallholders in Johor. This research aim is to study the technical efficiency, profitability status and socio-economic factors of the smallholders in Johor. Data collected from the questionnaires that were distributed in 2015 to 88 respondents were then analysed using DEA to evaluate the technical efficiency. Research suggested that the smallholders are inefficient with a TE score VRS = 0.83 and only 8 smallholders were fully efficient. The variables that are affecting the smallholder's technical efficiency are age, education level, land size, labour utilization, seeds density, chemical application, and fertilizer, while the farming experience had a negative effect on the technical efficiency. With a subsidy, the benefit-cost ratio for Moris variety is 1.00: 1.69 compared to 1.00: 1.62 for Josapine variety. Although the selling price for Josapine is higher than Moris, but Moris is more profitable because of it perishable rate is lower than the Jospaine. These findings could be used as a baseline data by the relevant parties or agencies involve in improving the pineapple farmers' productivity and profitability.